ChemInform Abstract: Catalytic Asymmetric Reactions by Metal and Chiral Phosphoric Acid Sequential Catalysis. Issue 48 (2nd December 2014) - Yang, Ze‐Peng; Zhang, Wei; You, Shu‐Li
Abstract Review: [62 refs.